Corrosion and mechanical properties of cast aluminium alloys. (December 2013) - Okayasu, M.; Takeuchi, S.; Shiraishi, T.
Abstract : The corrosion and mechanical properties of cast aluminium alloys [ADC6(Al–Mg) and ADC12(Al–Si–Cu)] have been investigated. Specifically, cast samples with different microstructural characteristics were produced using two different casting techniques, namely, gravity casting (GC) and heated mould continuous casting (HMC). For ADC6, intergranular corrosion occurs mainly through the eutectic Mg2 Si and Al6 (Mn, Fe) phases and the precipitate free zone around the eutectic structures. On the other hand, pitting corrosion in the α -Al phase is the dominant feature for ADC12. Such corrosion characteristics can be interpreted from the material properties (polarisation resistance and electrode potential) of the individual structures, such as the α -Al phase, eutectic α -Al phase and precipitate phase. It also appeared that the extent of corrosion is affected by the size of the microstructure; the ADC6 sample with small second phases has a high corrosion resistance due to the limited area for corrosion. In addition, the higher proportion of solid solution in the α -Al phase of ADC6, arising from the high cooling rate, makes a high corrosion resistance because of the change of electrode potential. A different trend is obtained for ADC12 due to the pitting corrosion, where low corrosion resistance is obtained for the sample with tiny grain. The tensile strength and ductility for both HMC samples (ADC6 and ADC12) are higher than those for the GC equivalents, which is caused by the presence of tiny microstructures and uniform crystal orientation. However, the mechanical properties of HMC samples decrease dramatically during corrosion, although these are still high compared to those of the GC samples without corrosion.